SINERGITAS PROGRAM “FANTASTIC! PONOROGO” DALAM RANGKA PEMBANGUNAN PARIWISATA BERBASIS COLLABORATIVE GOVERNANCE DI KABUPATEN PONOROGO - Irfan Nugroho; Yusuf Adam Hilman (Jurnal Ilmiah Wahana Bhakti Praja, 2020)
ABSTRACT. "Fantastic!Ponorogo" is a tourism development program coordinated between the vision and mission of the Ponorogo Regency in disassemble in RPJMD 2016 - 2021. This talk about studying RPJMN, RPJMD, Province Of East Java, and RPJMD Ponorogo Regency. 2019 was a tourist visit to East Java. The implementation of the collaborative governance practices described the processes partnership between the government and the private sector, aimed at optimizing the objectives of the activities. The purpose of this research is to find out the synergy "Fantastic!Ponorogo" to collaborative governance practices in the tourism sector conducted in Ponorogo Regency. In this study in qualitative research. The collaborative governance showS synergy, effective, and successful because of some factors, including 1). The commitment by the Bupati, vice-regent, and all his staff the government Ponorogo Regency in this case the head of supportive tourism of the year 2019, 2). A, collaboration connectivity among stakeholders, 3)The enthusiastic people who are active in various events held, 4). The basis for the government in government duty. Key words: Sinergitas; Colaborative Governance; Fantastic! Ponorogo, Pembangunan Pariwisata